Quality indicators in colonoscopy: an evolving paradigm. Issue 3 (21st February 2020) - Shine, Rebecca; Bui, Andrew; Burgess, Adele
Abstract: The year 1969 marked a revolution in the diagnosis of colorectal cancer (CRC). It is when Dr Wolff developed the colonoscope and quickly realized its potential in both diagnosis and treatment of colonic neoplasms. Over the past 50 years there has been exponential increase in utilization of colonoscopy with over 1 million colonoscopies performed annually throughout Australasia. Endoscopic removal of pre‐malignant lesions has been proven to reduce the incidence and mortality of colorectal. Although timing and frequency of surveillance colonoscopy plays a crucial role in risk reduction of CRC, this is dependent upon the findings of the index colonoscopy. The goal of screening colonoscopy is to detect CRC and identify and remove pre‐malignant neoplasms that risk progression to CRC. With increasing uptake of bowel screening throughout Australasia, there is increasing pressure to ensure all endoscopists and endoscopy units perform at a universal high‐quality. All too often high demand and constant delays compromise colonoscopy quality. Without clear and concise quality indicators with transparent measurement and audit, these flaws can quickly jeopardize screening goals and patient outcomes. This review aims to explore six key quality indicators and explore the evidence behind the current recommended standards. These key indicators include; rate of adequate bowel preparation, caecal intubation rate, adenoma detection rate, withdrawal time, complication rates and surveillance intervals. Abstract : High‐quality colonoscopy is imperative for screening and surveillance for colorectal cancer. There has been a recent surge on the emphasis of quality indicators and this review highlights six key quality indicators and the evidence and rationale behind them.